Preparation and analysis of structural, morphological and optical properties of BaFeO2.67/Fe2O3 nanocomposite - Adnan Alnehia; Annas Al-Sharabi; Muhammad Hadi; M. A. Ahlam (Scientific Reports)
Abstract This research presents the synthesis of BaFeO2.67/Fe2O3 nanocomposite using a simple chemical co-precipitation method without any capping agents, which distinguishes it from existing methodologies. The study provides a comprehensive investigation into its structural, morphological, and optical properties. X-ray diffraction (XRD) analysis confirmed the formation of a hexagonal crystalline structure with an average crystallite size of approximately 40.50 nm. Fourier-transform infrared spectroscopy (FTIR) identified key functional groups, further establishing the compound’s unique characteristics. Notably, surface potential measurements revealed a net surface charge of -20.85 ± 0.50 mV, indicating excellent stability, which is critical for practical applications. Scanning electron microscopy (SEM) illustrated rough surfaces with irregularly shaped agglomerates, suggesting strong interactions between barium (Ba) and iron (Fe). Energy-dispersive X-ray spectroscopy (EDX) validated the presence of Ba, Fe, and O elements. Furthermore, optical analyses demonstrated a band gap energy of 2.09 eV, positioning this nanocomposite as a promising candidate for applications in catalysis, magnetic materials, and optoelectronic devices. This work not only contributes to the understanding of BaFeO2.67/Fe2O3 nanocomposites but also opens new avenues for their application in advanced technological fields.